(untitled) (Revista Electrónica Calidad en la Educación Superior, 2017)
At the University of Chile, since 2013 a new entrance system has been implemented for students of excellence in the academic trajectory that come from public establishments of high vulnerability. Objective: To know the experience of the students that enter by equity quotas to the School of Obstetrics between the years 2013 to 2016. Methods: Case studies. A questionnaire was applied to the students and interviews were held with the teachers. Results: The dropout rate was 41%, whose main cause was vocational. 90% of the students who still remain present reprobation. According to the students and teachers, the main obstacles were the lack of study techniques and the lack of knowledge in basic sciences. Conclusions: The experience for the students is gratifying, since it assures them the entrance to the University. However, it is frustrating for them to realize all the theoretical shortcomings they have, as a result of the inequalities that exist in education in Chile. It is necessary to rethink the support strategies so that they are perceived as help and not as academic overload.